Answers

The Brainliest Answer!
2015-03-20T21:34:27+05:30
In the trapezium AB // DC,
So ar(ABD) = ar(ABC) {on same base and between same parallels}
= ar(ABD) - ar(AOB) = ar(ABC) - ar(AOB
= ar(AOD) = ar(BOC)

Hope that helps !!
2 5 2
2015-03-20T22:39:18+05:30
In trapezium ABCD , as triangle DAB and triangle CAB lie on same base AB and between same parallels AB parallel to CD , so area ADB equals to area ACB
subtract area AOB from b I th sides, area ADB - AOB = area CAB -AOB          
 
So area AOD = area COB
hence proved


1 5 1